Values of local wisdom in Dayak Kanayatn’s folktale: A sociology study of literature - Seli, Sesilia; Anggelina, Marsiana (Universitas Lampung, 2022)
The folk tales of Dayak Kanayatn reflect world views, traditions, and various local values that are useful for educating the younger generation. Thus, as the heirs, in addition to having extensive knowledge, they also have noble morals passed down from their ancestors through folklore. The objective of this study was focused on the analysis and interpretation of local traditions and values contained in 16 folk tales. This study was based on folklore theory, local values, and sociology of literature using a qualitative descriptive method, and a sociological approach to literary works. The results of the analysis and interpretation show that the values of local wisdom contained in the Dayak Kanayatn folklore include: (1) local wisdom values that reflect the relationship between humans and God, including (a) belief in the existence of Jubata (God) and (b) always having tribe; (2) the values of wisdom that reflect the relationship amongst humans which include the values of (a) solidarity; (b) obedience to customs and traditions; (c) deliberation and cooperation; (d) respect to guests; (e) respect to gender equality; (f) respect for parents; (g) love for family, (h) upholding friendship; and (3) the values of local wisdom that reflect the relationship between humans and nature, including (a) respecting nature/forests; (b) belief in natural signs; (c) reliance on nature; and (d) belief in supernatural things.